The university student experience of face-to-face and online discussions: coherence, reflection and meaning - Robert A. Ellis; Peter Goodyear; Agi O'Hara; Michael Prosser (Association for Learning Technology, 2007)
This paper reports on an investigation into learning through discussions by undergraduate social work students. Second-year students studying psychology for social work experienced discussions began with face-to-face tutorials, and then continued for some time after online. This study used closed-ended questionnaires to investigate what students thought they were learning through discussions (their concepts), and how they engaged in the discussions face-to-face and online (their approaches). Significant associations were found among students' concepts of discussions, approaches and levels of achievement. The results suggest that students who do not understand how discussions can help them to interrogate, reflect on and revise their ideas tended not to approach either face-to-face or online discussions in ways likely to improve their understanding or their levels of achievement. This type of insight is critical for teacher/designers wishing to create university experiences in which discussion is used to promote learning.